Screen on = development off? A systematic scoping review and a developmental psychology perspective on the effects of screen time on early childhood development - Sticca, Fabio; Brauchli, Valérie; Lannen, Patricia (Frontiers in Developmental Psychology, 2025)
Research on the associations between screen time and child development suggests that various forms of screen time might pose a risk for various aspects of child development. However, data on the impact of exposure to screen media on the development of children under 3 years of age is comparatively scarce. Although the evidence available on the topic is evolving rapidly, no review of existing literature has yet encompassed a comprehensive set of developmental outcomes with a focus in the first 3 years of life. To address this research gap, the present literature review focused on the influences of screen time on various developmental outcomes of children aged zero to 36 months. These outcomes were sleep-related parameters, physical health, cognition, learning efficiency, language, motor skills, socio-emotional skills, social interaction, and overall development. To this end, ten databases were searched systematically, and 158 studies that were published between the launch of the iPhone in early 2007 until 2024 were included. Only studies that reported specific results for the age range of zero to 36 months were examined, including longitudinal studies with samples of children aged zero to 36 months at the first wave of assessment. For most outcomes, a comparable amount of undesirable and non-significant associations was found with children's screen time, while few desirable associations were reported. In line with the notion of resilience, these results indicate that characteristics of the child, the context, and/or the content moderate the associations between screen time and child development in early childhood, thus contributing to mitigating the potential of displacement of learning opportunities or even creating new learning opportunities. More studies with designs that can examine the causal effect of screen time on child development and that explicitly address the role of child, content, and context variables are needed.